Dielectric Sensors Based on Electromagnetic Energy Tunneling - Omar Siddiqui; Mani Kashanianfard; Omar Ramahi (Sensors, 2015)
We show that metallic wires embedded in narrow waveguide bends and channels demonstrate resonance behavior at specific frequencies. The electromagnetic energy at these resonances tunnels through the narrow waveguide channels with almost no propagation losses. Under the tunneling behavior, high-intensity electromagnetic fields are produced in the vicinity of the metallic wires. These intense field resonances can be exploited to build highly sensitive dielectric sensors. The sensor operation is explained with the help of full-wave simulations. A practical setup consisting of a 3D waveguide bend is presented to experimentally observe the tunneling phenomenon. The tunneling frequency is predicted by determining the input impedance minima through a variational formula based on the Green function of a probe-excited parallel plate waveguide.